Biomarkers of Chronic Kidney Disease - Mineral and Bone Disorder (CKD-MBD), A Review of Published Patents and Patent Applications - Rothe, Hansjorg; Liangos, Orfeas; Ketteler, Markus (Recent Patents on Biomarkers, 2012)
The aim of this article is to investigate patents and patent applications to the US Patent and Trademark Office, which are related to chronic kidney disease mineral and bone disorder (CKD-MBD). This term stands for a certain concept, which interprets bone disease of chronic kidney disease in a wider clinical context including coronary artery disease, extraosseous calcification and endocrine disorders. This concept which was introduced in 2005 is explained in detail and the related patents and biomarkers are discussed. Included in the article are also patents claiming new roles, unrelated to CKD-MBD as such, for some of the key biomarkers in this area. These include such promising compounds as klotho and FGF-23, matrix-Gla protein or fetuin-A. The patents dealing with these biomarkers outline a great potential for diagnostics and therapy not only of CKD patients in the future. Thanks to advances in cloning and sequencing techniques of recent years, a big proportion of the listed biomarker patents describe gene products identified by the analysis of rare genetic conditions. Also, some new roles for already well established markers such as parathormone (PTH) or vitamin K claimed by patent applicants are discussed in the article.
Keywords: matrix Gla-protein